Leaf traits variation of arabica coffee cultivars in response to population density and mineral nutrient - Tamirat, W.; Gobena, A.; Kufa Obso, T. (2020)
Leaf trait is good predictors of plant performance. It is closely associated with light requirement, growth and survival of the plant. This study was designed to evaluate the effect of seedling planting density and fertilizer rate on leaf traits variation of two Arabica coffee cultivars under nursery conditions. It was conducted at Jimma Agricultural Research Center from (February 29 to October 29), 2018. A factorial experiment was used and treatments were arranged using completely randomized design with three replications. Treatments consisted of combinations of two Arabica coffee cultivars (74110 and 75227), four population densities (one, two, three and four plants per polythene tube) and three compound NPK (22:6:12 + Te) rates (control, 5g and 10g). The results showed that interaction between cultivar, population density and fertilizer was significantly (P ≤ 0.05) influenced LN, LPR and LAI, and highly significantly (P ≤ 0.01) influenced LWR and SLA. High planting density (PD2) with 5g of NPK enhanced LN and LPR in cultivar-74110 while conventional (PD1) with 5g of NPK enhanced LN and LPR in cultivar-75227. Highest value of LWR was recorded from high planting density (PD2) with 5g of NPK while maximum value of LAI and SLA was recorded from high planting density (PD3) with 5g of NPK for both cultivars. At early field planting time, coffee seedling with higher LAI and SLA are very important for efficiently capture and better utilization of solar energy or light as well as increase seedling growth. In general, planting high population density (PD3) and fertilized with 5 g of NPK seems sufficient to improve LAI and SLA of coffee seedlings. Therefore, the future research direction should be focused on the management for increase leaf traits under field conditions.